Transcriptional profiling of human microglia reveals grey–white matter heterogeneity and multiple sclerosis-associated changes - Marlijn van der Poel (Nature Portfolio, 2019)
It is unclear if early pathological changes in normal-appearing multiple sclerosis (MS) tissue are reflected by molecular changes in microglia, which might contribute to lesion initiation. Here, authors demonstrate significant intrinsic differences in the human microglial transcriptome between grey and white matter regions, isolated from MS and non-neurological control donors, and show early microglial changes related to MS pathology.